La gimnasia básica como estrategia para fortalecer la motricidad gruesa en estudiantes del subnivel medio. - Ordoñez Espinoza, Carlos Ariel (Machala : Universidad Técnica de Machala, 2022)
This research work is an integrative project, and focused on Basic Gymnastics and strategies to strengthen gross motor skills, whose objective was to analyze the practices of basic gymnastics for strengthening gross motor skills in students of the medium sublevel, for which the objects of study were characterized for the theoretical foundation, In addition, basic gymnastics practices were identified to strengthen gross motor skills; himself, the orientation that physical education teachers need in the subject of study was identified. The data collection was based on the qualitative approach, interview and observation. With a non-experimental - descriptive methodology and the methods with the highest incidence were, bibliographic, analytical and synthetic. For the purpose of collecting the information, the interview that was directed to the director and the observation of a class were used, managing to diagnose the reality in the Juan Montalvo basic education school. In relation to the sample, it was considered that during physical education class basic gymnastics activities are not carried out with the students, causing limitations in the development of gross motor skills; This work was organized by four dimensions such as basic gymnastics, gross motor skills, Educational Proposal, Teaching Experience and consequently the indicators served as a guide for the elaboration of qualitative research instruments that facilitated the reception of opinions and attitudes of the people related in this inquiry and at the same time analyze the information collected. The results of this research were aimed at physical education teachers to stimulate through an exercise guide on basic gymnastics that would contribute to strengthening gross motor skills. On the other hand, it was specified that basic gymnastics should be applied to the teacher in physical education classes for the strengthening of gross motor skills in students through movements, body agility, dances and dance in which they have a little of knowledge regarding the subject since it was possible to show that through these activities it contributes to the development and strengthening of gross motor skills. In addition, this work includes a proposal that was composed of four phases of implementation aimed at teachers who assume the subject of Physical Education, in addition, the logistical resources and the assessment of the feasibility with the dimensions, technical, economic, social and environmental were included, demonstrating the capacity to achieve the objectives of the proposal, determining the viability and material capacities that the executed parts of the project have. Proposal.
El presente trabajo de investigación se trata de un proyecto integrador, y se centró en la Gimnasia Básica y las estrategias para fortalecer la motricidad gruesa, cuyo objetivo se orientó en analizar las prácticas de la gimnasia básica para el fortalecimiento de la motricidad gruesa en estudiantes del subnivel medio, para lo cual se caracterizó los objetos de estudio para la fundamentación teórica, además se identificó las prácticas de la gimnasia básica para el fortalecimiento de la motricidad gruesa, a sí mismo se identificó la orientación que necesitan los docentes de educación física en el tema de estudio. La recopilación de datos se fundamentó desde el enfoque cualitativo, entrevista y observación. Con una metodología de carácter no experimental - descriptivo y los métodos de mayor incidencia fueron: el bibliográfico, el analítico y sintético. Para efecto de recopilar la información se utilizó la entrevista que estuvo dirigida al directivo y la observación de una clase, logrando diagnosticar la realidad en la escuela de educación básica Juan Montalvo. En relación a la muestra se consideró que durante las clases de educación física no se realizan actividades de gimnasia básica con los estudiantes, provocando limitaciones en el desarrollo de la motricidad gruesa este trabajo estuvo organizado por cuatro dimensiones como la gimnasia básica ,motricidad gruesa , propuesta educativa, experiencia docente y en consecuencia los indicadores sirvieron de guía para la elaboración de los instrumentos de investigación cualitativa que facilitó la recepción de opiniones y actitudes de las personas relacionadas en esta indagación y al mismo tiempo analizar la información recopilada. Los resultados de esta investigación fueron orientados a los docentes de educación física para estimular a través de una guía de ejercicios sobre la gimnasia básica que contribuiría al fortalecimiento de la motricidad gruesa. Por otra parte, se concretó que la gimnasia básica debe ser aplicado al docente en las clases de educación física para el fortalecimiento de la motricidad gruesa en estudiantes a través de los movimientos, agilidad del cuerpo, los bailes y la danza en la cual tienen un poco de conocimiento respecto al tema ya que se pudo evidenciar que mediante estas actividades contribuye al desarrollo y al fortalecimiento de la motricidad gruesa. A demás este trabajo incluye una propuesta que estuvo compuesta de cuatro fases de implementación dirigidas a los docentes que asumen la asignatura de Educación Física, además se incluyó los recursos logísticos y la valoración de la factibilidad con las dimensiones, técnica, económica, social y ambiental, demostrando la capacidad para lograr los objetivos de la propuesta, determinando la viabilidad y capacidades materiales con los que cuentan las partes ejecutaros de la propuesta.
Keywords: GIMNASIA BASICA; ESTRATEGIA; MOTRICIDAD GRUESA; PRACTICA LUDICA